Cell-free protein synthesis for nonribosomal peptide synthetic biology - Sword, Tien T.; Abbas, Ghaeath S. K.; Bailey, Constance B. (Frontiers in Natural Products, 2024)
Peptide natural products have a wide range of useful applications as pesticides, veterinary agents, pharmaceuticals, and bioproducts. To discover new natural products, manipulate them for analog generation, and to harness the potential of these bioactive compounds for synthetic biology, it is necessary to develop robust methods for the expression of biosynthetic genes. Cell-free synthetic biology is emerging as an important complementary approach because it is highly desirable to express protein on a more rapid timescale and does not rely upon the genetic tractability of a strain thus improving the throughput of design-build-test-learn (DBTL) cycles. Additionally, generating metabolites outside the cell can overcome issues such as cellular toxicity which can hamper applications like antibiotic development. In this review, we focus on the cell-free production of peptide natural products generated by non-ribosomal peptide synthetase. Nonribsomal peptides are biosynthesized by non-ribosomal peptide synthetases (NRPSs) which are large "mega" enzymes that provide specific challenges to heterologous expression. First, we summarize NRPSs and their corresponding peptide metabolites that are expressed in cell-free systems. With that, we discuss the requirements and challenges to express such large proteins in cell-free protein synthesis as well as host machineries that have been developed for cell-free protein synthesis that could be particularly relevant to generating non-ribosomal peptide metabolites in the future. The development of cell-free systems can then be used for prototyping to accelerate efforts towards engineered biosynthesis of these complex pathways.